Pengaruh Marketing Mix 7P Terhadap Minat Beli Konsumen Di Dodolan Coffee Solo - Apnes Nur Setiyawan; Indah Wahyu Utami; Fery Wisnu Saputro (Politeknik Kampar, 2024)
The current business development is quite rapid, especially in the coffee shop business so that the competition between businesses is also increasing, so there is a need for a strategy to attract consumers. The 7P marketing mix strategy is a strategy that can increase product sales by increasing product competitiveness in order to get maximum profit on target. This study aims to determine the marketing mix strategy, as well as the variables that can influence consumer buying interest at the Dodolan Coffe coffee shop. Data collection through interviews, questionnaires, observation and literature study. The results of the study from 95 respondents obtained that from the F test the marketing mix variable 7P simultaneously had a significant effect on purchasing decisions for Dodolan Coffe products of 0.000 <0.05 and the calculated F value was 66.947 > F table 1.86. Other results using the T Test on the decision to buy Dodolan Coffee products, there are 3 variables (People, Promotion, Process) that are influential so that it must be considered, then there are 4 variables (Place, Product, Price, Physical Evidence) that have no effect so they are not a top priority in increasing consumer purchasing power.